2006
DOI: 10.1002/ep.10129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the AERMOD dispersion model as a function of atmospheric stability for an urban area

Abstract: The AERMOD dispersion model was used to compute ambient air concentrations of SO 2 for 1-, 3-, and 24-h

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 7 publications
(8 reference statements)
0
45
0
4
Order By: Relevance
“…The factor of 2 statistic describes the percentage of data where model-predicted concentrations are within a factor of 2 of observed data. This value ranges from 14 to 43% across the six sites, lower than the 50-80% requirement for a good model (Chang and Hanna, 2004;Kumar et al, 2006).…”
Section: Scientific Model Validationmentioning
confidence: 72%
See 2 more Smart Citations
“…The factor of 2 statistic describes the percentage of data where model-predicted concentrations are within a factor of 2 of observed data. This value ranges from 14 to 43% across the six sites, lower than the 50-80% requirement for a good model (Chang and Hanna, 2004;Kumar et al, 2006).…”
Section: Scientific Model Validationmentioning
confidence: 72%
“…The unfilled circle corresponds to the population mean with error bars representing the 95% confidence interval around the mean. The shaded area represents the range of values acceptable for a "good model," as defined by Chang and Hanna (2004) and Kumar et al (2006). performance, as even small instrumentation errors or shifts in wind direction can cause a spatial displacement between model predictions and observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For air quality modelling for various perspectives with measured values of concentration, AERMOD has been applied. AERMOD was used for different time scales which could help chronical exposure assessment in epidemiological studies (Kumar et al, 2006;Zou et al, 2010). Kumar et al (2006) used AERMOD to predict concentration for the 1-h, 3-h and 24-h averaging period for Lucas county, Ohio, USA.…”
Section: Application Of Aermod For Impact Assessmentmentioning
confidence: 99%
“…It was found that the shear layer model over predicts the concentration for all windy conditions except for few data points. The statistical evaluation based on the work of Hanna et al (1993), Gudivaka and Kumar (1990), Riswadkar and Kumar (1994) and Kumar et al (2006), was used in this study. In order to determine the significance of the evaluation of the model, four statistical parameters; normalized mean square error (NMSE), fractional bias (FB), correlation coefficient (R), and geometric mean bias (MG) were calculated.…”
Section: Model Evaluation Using Measured Datamentioning
confidence: 99%